Perancangan Aplikasi Inventori Untuk Mengelola Persediaan Barang Pada Toko Jamu Menggunakan Metode FIFO, LIFO Dan Average (Studi Kasus : Toko Jamu Mujur Jaya Cisoka) - Ridwan, Muhamad; Apriyanto, Budi (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2023)
Technological developments are increasingly increasing, encouraging human nature to make the best use of and use technology. The emergence of various types of electronic devices and applications that are growing along with the development of the internet can now be felt almost anywhere. In addition, the current development of computers plays an important role in various fields of business, especially its good ability to process data and information. Mujur Jaya Cisoka is a Jamu Shop that sells various types of Jamu (Raw), Herbal Ingredients, Medicines and so on. In its implementation, data management and data processing are still carried out using conventional methods, for example in stock data storage, sales data are still recorded using stationery, so that data retrieval takes longer, therefore, an Inventory Application is needed for managing goods data. making it easier for store employees to manage item data. In this Inventory Application, in the process the writer uses the FIFO, LIFO and Average methods. Design and implementation is focused on the process of managing the inventory of goods carried out by employees or shop clerks under the supervision of the shop owner. In the final stage of developing this application, an evaluation of the application development process is carried out. What things have been made and what are the shortcomings in application development, will be reviewed in this thesis.